Effects of different carbohydrate levels on glycolipid metabolism and liver health of channel catfish (Ictalurus punctatus) - Xiaochen Ma; Qisheng Lu; Guoli Han; Jinglu Jia; Jingyue Cao; Haokun Liu; Junyan Jin; Zhimin Zhang; Yunxia Yang; Xiaoming Zhu; Dong Han; Shouqi Xie (Aquaculture Reports)
This study evaluated the effects of dietary carbohydrate levels on glycolipid metabolism and liver health of channel catfish. Six isonitrogenous and isolipidic diets with corn starch contents of 10 % (C10), 15 % (C15), 20 % (C20), 25 % (C25), 30 % (C30) and 35 % (C35) were set up. After 8-week feeding trial, there was no significant difference in the growth performance of all groups (P > 0.05). The study showed that C30 and C35 groups significantly increased plasma glucose levels, activated the expression of glycolysis-related genes (gk, hk, pklr, pfk) and mitochondrial oxidative phosphorylation related genes (ndufa1, sdhb, sdha, cytb-c1, cox, atp5fa1, atp5f1b), and repressed the expression of gluconeogenesis-related genes (pc, fbp, pepck, g6p) in the channel catfish (P < 0.05). The upregulation of glycogen synthesis-related genes (ppp1r3g, ppp1r3c, ppp1r3b, gys, gnl, ugp2a, ugp2b) contributed to a significant increase in hepatic glycogen content. In addition, C30 and C35 groups significantly increased the expression of pentose phosphate pathway related genes (g6pd, 6gpd), while C10 to C25 groups glucose metabolism-related pathways did not exhibit significant differences. Hepatic triglyceride and cholesterol results showed that C30 and C35 groups induced excessive lipogenesis, activated the expression of lipogenesis-related genes (acc, acly, vldlr) and cholesterol synthesis-related genes (srebf2, hmgcr, sqle). In C30 and C35 groups also increased the hepatic ALT, AST and MDA levels, activated the expression of injury-related genes (a-sma, tgf-β), inflammation-related genes (tnf-α, il-1β, il-6) and apoptosis-related genes (baxb, caspase-3, caspase −10) (P < 0.05). C35 group significantly further increased the expression levels of stress genes such as hamp, hsp70 and hsp90 (P < 0.05), while there were no significant differences in the levels of lactate and cortisol in all groups (P > 0.05). In conclusion, our results suggest that dietary carbohydrate levels less than 30 % will not impair the health and growth performance of the channel catfish.